2007
DOI: 10.1073/pnas.0705495104
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal population coding of continuous and discrete quantity in the primate posterior parietal cortex

Abstract: Quantitative knowledge guides vital decisions in the life of animals and humans alike. The posterior parietal cortex in primates has been implicated in representing abstract quantity, both continuous (extent) and discrete (number of items), supporting the idea of a putative generalized magnitude system in this brain area. Whether or not single neurons encode different types of quantity, or how quantitative information is represented in the neuronal responses, however, is unknown. We show that length and numero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
209
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(221 citation statements)
references
References 43 publications
12
209
0
Order By: Relevance
“…Each of these neurons is tuned to a preferred numerosity value (e.g., 4), but also fires when close numerosities are presented (3 and 5, 6), and thus represent numbers only approximately, in a format which would be suitable to encode continuous quantities. Recently, Tuduscius and Nieder (2007) tested whether the numerositysensitive neurons in the IPS were also sensitive to line length (a continuous variable). They found that the populations encoding these two attributes overlapped partially: 11.5 and 10% of the neurons were activated for physical size and numerosity, respectively; whereas, 3.5% fired for both physical size and numerosity.…”
Section: Evidence From the Comparative Literaturementioning
confidence: 99%
“…Each of these neurons is tuned to a preferred numerosity value (e.g., 4), but also fires when close numerosities are presented (3 and 5, 6), and thus represent numbers only approximately, in a format which would be suitable to encode continuous quantities. Recently, Tuduscius and Nieder (2007) tested whether the numerositysensitive neurons in the IPS were also sensitive to line length (a continuous variable). They found that the populations encoding these two attributes overlapped partially: 11.5 and 10% of the neurons were activated for physical size and numerosity, respectively; whereas, 3.5% fired for both physical size and numerosity.…”
Section: Evidence From the Comparative Literaturementioning
confidence: 99%
“…Although some neurons responded only to numerosity and others only to line length, a subset of cells (∼20%) responded to both magnitudes of line length and numerical value. These and other studies, including functional MRI studies of adults, have led some researchers to argue for a "distributed but overlapping" representation of different magnitudes at the neural level (4,8,61). Simply put, different types of magnitude representation, including size, number, and time (and possibly others such as brightness), share some neural resources in parietal cortex but not others.…”
Section: For Review)mentioning
confidence: 99%
“…Moreover, some data even suggest that a single parietal neuron can represent more than one type of magnitude. In one study (61), monkeys were trained to perform a line-length matching task and a numerical matching task. During stimulus presentation as well as a subsequent delay, single neurons in the IPS responded selectively to visual stimuli according to their numerosity or length.…”
Section: For Review)mentioning
confidence: 99%
“…These representations are assumed to be automatic in the sense that they are not affected by task demands. At a later stage, abstract representations may emerge in accordance with the task requirements in the prefrontal cortex, which is associated with training effects, working memory and strategy application (see also Gilbert & Burgess 2008;Tudusciuc & Nieder, 2007).…”
Section: Number Range Effectmentioning
confidence: 99%
“…These representations are assumed to be automatic in the sense that they are not affected by task demands. At a later stage, abstract representations may emerge in accordance with the task requirements in the prefrontal cortex, which is associated with training effects, working memory and strategy application (see also Gilbert & Burgess 2008;Tudusciuc & Nieder, 2007).The objective of the present study was to explore whether the granularity or resolution of the evoked mental number line can also be changed by context. Consider a numerical comparison task, in which participants are presented with pairs of numbers (one pair at a 5 NUMBER RANGE EFFECT time) and are asked to select the larger number in each pair.…”
mentioning
confidence: 99%